Life Based on Husnudzon and Divine Orientation: An Interview Study of H.R. Figures on the Philosophy of Life in the Perspective of Islamic Ethics - Akilah, Hanan; Diponegoro, Ahmad Muhammad (Indonesian Journal of Multidisciplinary Science, 2026)
This research aims to examine the philosophy of life of a character with the initials H.R., who emphasizes the values of kindness toward Allah and humankind, the principle of loving and hating for Allah’s sake, and a life orientation based on intentions devoted to Allah. This study uses a descriptive qualitative approach with semi-structured interview techniques, supported by data reinforcement through a literature review. The results indicate that the philosophy of life applied by H.R. is derived from Islamic teachings that integrate spiritual and social dimensions into daily practices. These findings are further reinforced through literature analysis and references to relevant Qur’anic verses and hadiths aligned with the research focus. This article is expected to contribute to a deeper understanding of the significance of the Islamic philosophy of life in shaping personal ethics, psychological peace, and the quality of social relationships in the context of modern life. Furthermore, the study shows that a God-centered life orientation plays an essential role in fostering balance between faith, moral reflection, and social reality, thereby encouraging the development of a responsible attitude.